The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5194/jsss-2-73-2013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of coatings within liquid-filled tubes and containers by mode conversion of leaky Lamb waves

Abstract: Abstract. In this paper, a new acoustic sensor principle for coating detection within liquid-filled tubes and containers based on mode conversion of leaky Lamb waves is introduced. Leaky Lamb waves are excited and detected by single-phase transducers, which are attached on the outer side of a tube or container. By transmission time and amplitude measurements, coating formation within the liquid-filled tube and container is detected non-invasively. This new sensor principle is subdivided into the separate consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…Manufactures used different contact and contactless approaches to overcome build-up effects. An acoustic principle based material coating detection sensor was also reported in [7] which operates on the principle of lamb wave's mode conversion. Due to the presence of material's coating in the container wall, the propagation time of waves are changed, resulting in the alteration of the waves properties and is detected by implementing two receivers on the outer side of the container wall.…”
Section: Introductionmentioning
confidence: 98%
“…Manufactures used different contact and contactless approaches to overcome build-up effects. An acoustic principle based material coating detection sensor was also reported in [7] which operates on the principle of lamb wave's mode conversion. Due to the presence of material's coating in the container wall, the propagation time of waves are changed, resulting in the alteration of the waves properties and is detected by implementing two receivers on the outer side of the container wall.…”
Section: Introductionmentioning
confidence: 98%
“…Several solutions are contributed to overcome the material coating problem in level detection approaches e.g. using electronic circuit in RF impedance based sensor, shielding effect in point detection sensor and high spray pressure washing in floating and ultrasonic sensor [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In this work a non-invasive ultrasonic approach has been realized by exciting Lamb-type guided acoustic waves on the outer surface of the wall of the tube by piezoelectric transducers and utilizing changes of their transmission behaviour along the tube wall, which reflect the formation of deposition layers on the inner surface of the pipe wall [ 10 , 11 , 12 , 13 , 14 ]. However, one has to be aware that in liquid-filled tubes with metallic walls Lamb wave modes and similar wave modes with sagittal displacements at the surface experience mode conversion into compressional waves in the liquid [ 15 , 16 ], which limits the range of inspection of the inner wall surface.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that proper mode and frequency selection is a crucial issue with respect to optimal sensitivity to film buildup in view of the complex wave structure of guided waves in solids [ 17 ]. In another approach, employing leaky A 0 Lamb-type waves excited and detected with wavelength-selective piezoelectric single-phase transducers and travelling on the tube wall in axial directions, a sensitivity to adhesive tape layers on the inner surface of a water-filled plastic tube has been demonstrated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%